Implementation of Innovative Learning Models to Increase Interest in Learning Sports Among Teenagers - Roma Wibero (Siber International Journal of Sport Education, 2024)
This study aims to examine the implementation of innovative learning models to increase teenagers’ interest in learning sports. Using a quantitative approach, data were collected through online questionnaires from 120 secondary school students. The results indicate that innovative learning models such as game-based learning, collaborative learning, and blended learning significantly enhance students’ enthusiasm, active participation, and motivation in sports education. Statistical analysis shows a positive and significant effect of these models on students’ learning interest, with a coefficient of determination (R²) of 0.48. Students reported that interactive and engaging methods make sports lessons more enjoyable and easier to understand. However, challenges such as limited facilities, time constraints, and technological access were noted as obstacles to optimal implementation. This study highlights the importance of adopting diverse and student-centered learning strategies in physical education to foster not only physical fitness but also social skills and self-confidence among teenagers. It is recommended that schools and educators support the continuous development and application of innovative learning approaches to improve educational outcomes in sports.